The measurement of child costs: A Rothbarth-Type method consistent with scale economies - Olivier Bargain; Olivier Donni (University College Dublin, UCD School of Economics, 2010)
We propose a new methodology to estimate the share of household income accruing to children (i.e., the cost of children). Following the principle of the Rothbarth approach, the identification of the children's share requires the observation of at least one adult-specific good. However, our method differs from this traditional approach in that it allows measuring economies of scale in the household and indifference scales in Lewbel (2003)'s sense. We illustrate the method with an application on the French Household Budget Survey.
hdl:10197/2632
Keywords: D11; D12; C30; D36; I31; J12; 330; Consumer Demand; Collective Model; Rothbarth Method; Cost of Children; Scale Economies; Equivalence Scales; Indifference Scales